Preparation of ZnWO4 Nanopowders and Its Bulk Type Single Crystal Growth by the Czochralski Method - Lim, C.S. (Asian Journal of Chemistry, 2011)
ZnWO4 nanopowders were prepared from polymeric complex method using microwave irradiation. The average crystalline sizes of the nanopowders were 18-25 nm showing an ordinary tendency to increase with the temperatures from 400 to 600 ºC. Bulk type single crystals of ZnWO4 were grown successfully in the [100], [010] and [001] directions using the Czochralski method. The effect of the growth parameters, such as the rotation speed, pulling rate and diameter of the grown crystals, were examined. The dislocation density on the (010) plane at the center of the crystal was lower than near the edge. The etch pit arrangement revealed the (100) slip plane to be most active during crystal growth. The hardness, thermal expansion coefficients and dielectric constants of the crystals were evaluated.